Drug Discovery for SARS-CoV-2 Utilizing Computer-Aided Drug Design Approaches - Jiao Guo; Yang Bai; Yan Guo; Meihua Wang; Xinxin Ji; Yang Wang (COVID)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a positive-sense RNA virus with an unusually large genome of approximately 30 kb. It is highly transmissible and exhibits broad tissue tropism. The third most pathogenic of all known coronaviruses, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is responsible for the clinical manifestation known as coronavirus disease 2019 (COVID-19), which has resulted in the loss of millions of lives on a global scale. This pandemic has prompted significant efforts to develop therapeutic strategies that target the virus and/or human proteins to control viral infection. These efforts include the testing of hundreds of potential drugs and thousands of patients in clinical trials. Although the global pandemic caused by the SARS-CoV-2 virus is approaching its end, the emergence of new variants and drug-resistant mutants highlights the need for additional oral antivirals. The appearance of variants and the declining effectiveness of booster shots are resulting in breakthrough infections, which continue to impose a significant burden on healthcare systems. Computer-aided drug design (CADD) has been widely utilized for predicting drug–target interactions and evaluating drug safety; it is regarded as an effective tool for identifying promising drug candidates to combat SARS-CoV-2. The CADD approach aids in the discovery of new drugs or the repurposing of United States Food and Drug Administration (FDA)-approved drugs, whose safety and side effects are already well established, thus making the process more viable. This review summarizes potential therapeutic agents that target SARS-CoV-2 or host proteins critical for viral pathogenesis, as identified using CADD approaches. Additionally, this study provides insights into the common in silico methods used in CADD and their current applications in the SARS-CoV-2 drug discovery process.